BENCHMARKING E-GOVERNMENT: CURRENT TRENDS AND DIGITAL BARRIERS TO DEVELOPMENT (International Journal of Innovative Technologies in Economy, 2021)
The basic principles and methodological foundations for measuring the readiness and ability of the national institutions to provide citizens and businesses with access to public services online are considered. On the occasion of the 20th anniversary of the study of the implementation of e-government tools in UN member states (UN E-Government Survey), current trends and transformations of the e-government model, the digital divide and digital barriers to further progress in the development of the digital economy and e-democracy are analyzed. The methodological basis of the study applied are techniques and methods of complex comparative analysis and logical generalization and the information base is formed by the results of the UN E-Government Survey and World Bank Governance Surveys.